Bibliometric studies and worldwide research trends on global health - Salmerón-Manzano, Esther; Manzano-Agugliaro, Francisco (International Journal of Environmental Research and Public Health, 2020)
Global health, conceived as a discipline, aims to train, research and respond to problems of a transboundary nature in order to improve health and health equity at the global level. The current worldwide situation is ruled by globalization, and therefore the concept of global health involves not only health-related issues but also those related to the environment and climate change. Therefore, in this Special Issue, the problems related to global health have been addressed from a bibliometric approach in four main areas: environmental issues, diseases, health, education and society.
Editorial de International Journal of Environmental Research and Public Health, volumen 17, número 16.
Keywords: COVID-19; asthma; pulmonary disease; HIV/AIDS; diabetes; medicinal plants; musculoskeletal risks; obesity; microplastics; climate change; wastewater treatment; patents; social networks; Scopus(2); JCR